A variant upstream of HLA‐DRB1 and multiple variants in MICA influence susceptibility to cervical cancer in a Swedish population. (7th January 2014) - Chen, Dan; Hammer, Joanna; Lindquist, David; Idahl, Annika; Gyllensten, Ulf
Abstract: In a genome‐wide association study, we have previously identified and performed the initial replication of three novel susceptibility loci for cervical cancer: rs9272143 upstream of HLA‐DRB1, rs2516448 adjacent to MHC class I polypeptide‐related sequence A gene (MICA), and rs3117027 at HLA‐DPB2 . The risk allele T of rs2516448 is in perfect linkage disequilibrium with a frameshift mutation (A5.1) in MICA exon 5, which results in a truncated protein. To validate these associations in an independent study and extend our prior work to MICA exon 5, we genotyped the single‐nucleotide polymorphisms at rs9272143, rs2516448, rs3117027 and the MICA exon 5 microsatellite in a nested case–control study of 961 cervical cancer patients (827 carcinoma in situ and 134 invasive carcinoma) and 1725 controls from northern Sweden. The C allele of rs9272143 conferred protection against cervical cancer (odds ratio [OR] = 0.73, 95% confidence interval [CI] = 0.65–0.82; P  = 1.6 × 10 −7 ), which is associated with higher expression level of HLA‐DRB1, whereas the T allele of rs2516448 increased the susceptibility to cervical cancer (OR = 1.33, 95% CI = 1.19–1.49; P  = 5.8 × 10 −7 ), with the same association shown with MICA‐A5.1 . The direction and the magnitude of these associations were consistent with our previous findings. We also identified protective effects of the MICA‐A4 (OR = 0.80, 95% CI = 0.68–0.94; P  = 6.7 × 10 −3 ) and MICA‐A5 (OR = 0.60, 95% CI = 0.50–0.72; P  = 3.0 × 10 −8 ) alleles. The associations with these variants are unlikely to be driven by the nearby human leukocyte antigen (HLA) alleles. No association was observed between rs3117027 and risk of cervical cancer. Our results support the role of HLA‐DRB1 and MICA in the pathogenesis of cervical cancer. Abstract : We have performed a large nested case–control cohort to validate findings in the first cervical cancer GWAS. We replicated the associations with rs9272143 located in the MHC class II region as well as with rs2516448 and MICA‐A5.1 in the class I region. In addition, we found protective effects of MICA‐A4 and MICA‐A5 against cervical cancer, attesting to the importance of the allelic variability at MICA for both recognition of infection and evasion of tumor surveillance.